2013
DOI: 10.1177/1362361313495965
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to bullying among students with autism spectrum conditions: A multi-informant analysis of risk and protective factors

Abstract: Research has consistently shown that children and young people with autism spectrum conditions are more likely to be bullied than those with other or no special educational needs. The aim of this study was to examine risk and protective factors that could help to explain variation in exposure to bullying within this group. A sample of 722 teachers and 119 parents reported on their child's experience of being bullied. This response variable was regressed onto a range of explanatory variables representing indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
81
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 70 publications
(116 reference statements)
9
81
2
1
Order By: Relevance
“…On a similar note, Rowley et al (2012) found that bullying increased in mainstream (as opposed to special) schools for children with less severe social impairments, perhaps reflecting the 'hidden' nature of the higherfunctioning forms of ASC. Finally, Hebron and Humphrey's (2013) multi-informant study found that behaviour difficulties, age, use of public transport, educational placement in mainstream settings, and being in receipt of SEND provision that involved external professional support were associated with increased exposure to bullying, with positive relationships and parental engagement emerging as protective factors in teacher-and/or parent-rated models. Taken together, these studies suggest there are a number of salient risk and protective factors for exposure to bullying among children and young people with ASC, although findings have been inconsistent for some variables (e.g.…”
Section: Risk and Protective Factorsmentioning
confidence: 97%
See 4 more Smart Citations
“…On a similar note, Rowley et al (2012) found that bullying increased in mainstream (as opposed to special) schools for children with less severe social impairments, perhaps reflecting the 'hidden' nature of the higherfunctioning forms of ASC. Finally, Hebron and Humphrey's (2013) multi-informant study found that behaviour difficulties, age, use of public transport, educational placement in mainstream settings, and being in receipt of SEND provision that involved external professional support were associated with increased exposure to bullying, with positive relationships and parental engagement emerging as protective factors in teacher-and/or parent-rated models. Taken together, these studies suggest there are a number of salient risk and protective factors for exposure to bullying among children and young people with ASC, although findings have been inconsistent for some variables (e.g.…”
Section: Risk and Protective Factorsmentioning
confidence: 97%
“…Gender is an underexplored area, and this is likely to reflect the higher rates of diagnosis in boys, meaning that fewer girls participate in studies. Only one study has explored this as a variable to date, with no significant differences found (Hebron and Humphrey 2013). Nevertheless, the potential for the nature of bullying to vary according to gender, as noted in the broader bullying literature (e.g.…”
Section: Risk and Protective Factorsmentioning
confidence: 99%
See 3 more Smart Citations